Antenatal and early infant predictors of postnatal growth in rural Vietnam: a prospective cohort study. Issue 2 (22nd September 2014) - Hanieh, Sarah; Ha, Tran T; De Livera, Alysha M; Simpson, Julie A; Thuy, Tran T; Khuong, Nguyen C; Thoang, Dang D; Tran, Thach D; Tuan, Tran; Fisher, Jane; Biggs, Beverley-Ann
Abstract : Objective: To determine which antenatal and early-life factors were associated with infant postnatal growth in a resource-poor setting in Vietnam. Study design: Prospective longitudinal study following infants (n=1046) born to women who had previously participated in a cluster randomised trial of micronutrient supplementation (ANZCTR:12610000944033), Ha Nam province, Vietnam. Antenatal and early infant factors were assessed for association with the primary outcome of infant length-for-age z scores at 6 months of age using multivariable linear regression and structural equation modelling. Results: Mean length-for-age z score was −0.58 (SD 0.94) and stunting prevalence was 6.4%. Using structural equation modelling, we highlighted the role of infant birth weight as a predictor of infant growth in the first 6 months of life and demonstrated that maternal body mass index (estimated coefficient of 45.6 g/kg/m 2 ; 95% CI 34.2 to 57.1), weight gain during pregnancy (21.4 g/kg; 95% CI 12.6 to 30.1) and maternal ferritin concentration at 32 weeks' gestation (−41.5 g per twofold increase in ferritin; 95% CI −78 to −5.0) were indirectly associated with infant length-for-age z scores at 6 months of age via birth weight. A direct association between 25-(OH) vitamin D concentration in late pregnancy and infant length-for-age z scores (estimated coefficient of −0.06 per 20 nmol/L; 95% CI −0.11 to −0.01) was observed. Conclusions: Maternal nutritional status is an important predictor of early infant growth. Elevated antenatal ferritin levels were associated with suboptimal infant growth in this setting, suggesting caution with iron supplementation in populations with low rates of iron deficiency.